Incremental effects of diabetes mellitus and chronic kidney disease in medial arterial calcification: Synergistic pathways for peripheral artery disease progression. (October 2019) - Krishnan, Prakash; Moreno, Pedro R; Turnbull, Irene C; Purushothaman, Meerarani; Zafar, Urooj; Tarricone, Arthur; Singla, Sandeep; Kini, Annapoorna; Sharma, Samin; Narula, Jagat; Badimon, Juan J; Purushothaman, K-Raman
Diabetes mellitus (DM) and chronic kidney disease (CKD) separately are known to facilitate the progression of medial arterial calcification (MAC) in patients with symptomatic peripheral artery disease (PAD), but their combined effect on MAC and associated mediators of calcification is not well studied. The association of MAC and calcification inducer bone morphogenetic protein (BMP-2) and inhibitor fetuin-A, with PAD, is well known. Our aim was to investigate the association of MAC with alterations in BMP-2 and fetuin-A protein expression in patients with PAD with DM and/or CKD. Peripheral artery plaques (50) collected during directional atherectomy from symptomatic patients with PAD were evaluated, grouped into no-DM/no-CKD ( n = 14), DM alone ( n = 10), CKD alone ( n = 12), and DM+CKD ( n = 14). MAC density was evaluated using hematoxylin and eosin, and alizarin red stain. Analysis of inflammation, neovascularization, BMP-2 and fetuin-A protein density was performed by immunohistochemistry. MAC density, inflammation grade and neovessel content were significantly higher in DM+CKD versus no-DM/no-CKD and CKD ( p < 0.01). BMP-2 protein density was significantly higher in DM+CKD versus all other groups ( p < 0.01), whereas fetuin-A protein density was significantly lower in DM+CKD versus all other groups ( p < 0.001). The combined presence of DM+CKD may be associated with MAC severity in PAD plaques more so than DM or CKD alone, as illustrated in this study, where levels of calcification mediators BMP-2 and fetuin-A protein were related most robustly to DM+CKD. Further understanding of mechanisms involved in mediating calcification and their association with DM and CKD may be useful in improving management and developing therapeutic interventions.